Sintered alkaline water electrolysis electrode catalyst as well as preparation method and application thereof
Through the preparation method of sintered alkaline water electrolytic electrode catalyst, the problem of the catalyst being easily fall off under high current density conditions is solved, the stability and reliability of the catalyst are improved, and it is suitable for application scenarios with continuous operation of high current density.
Patent Information
- Application Number
- CN202411484090.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-21
AI Technical Summary
The existing alkaline water electrolytic electrode catalysts are prone to fall off under high current density conditions, resulting in a degradation of catalytic performance and affecting the working efficiency and life of the electrolytic cell.
Using the preparation method of sintered alkaline water electrolytic electrode catalyst, a catalyst with high mechanical strength and chemical stability is prepared by mixing, pressing and sintering raw materials such as nickel powder, nickel-titanium alloy powder and alumina. .
It significantly improves the stability of the catalyst under high current density conditions, avoids the problem of catalyst shedding, enhances the catalytic performance and service life of the electrode, simplifies the production process, and reduces production costs.
Smart Images

Figure CN119491256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkaline water electrolysis, and in particular to a sintered alkaline water electrolysis electrode catalyst and a preparation method and application thereof. Background Art
[0002] At present, the electrode catalyst in the alkaline water electrolyzer is usually prepared by chemical deposition. The chemical deposition method forms a catalyst layer by depositing metal or alloy on the substrate, which can relatively simply prepare electrode materials with certain catalytic properties. It has the advantages of simple operation and low cost. In addition, the chemical deposition method can prepare a catalyst with a larger area in a shorter time, which is suitable for large-scale production.
[0003] Although the catalysts prepared by chemical deposition method show good catalytic performance in some application scenarios, under high current density conditions, the catalysts are easy to fall off from the substrate, resulting in decreased catalytic performance. For example, when the current density exceeds 6000A / cm², the stability of the catalyst prepared by chemical deposition method is significantly reduced, which seriously affects the working efficiency and life of the alkaline water electrolyzer. When the electrolyzer runs continuously at high current density for a period of time, the catalyst layer will gradually peel off, resulting in electrode failure.
[0004] The existing technology has solved the problem of large-scale preparation of catalysts to a certain extent, but the stability under high current density conditions still needs to be improved, especially in scenarios where continuous high current density operation is required. In view of this, the present invention provides a sintered alkaline water electrolysis electrode catalyst and its preparation method and application. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a sintered alkaline water electrolysis electrode catalyst and its preparation method and application. The purpose is to avoid the problem of catalyst shedding in the alkaline water electrolysis tank under high current density conditions, thereby improving the stability and reliability of the electrode.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, a method for preparing a sintered alkaline water electrolysis electrode catalyst comprises the following steps: (1) mixing raw materials of various electrode catalyst materials to obtain a mixed material, wherein the electrode catalyst material comprises the following raw materials: nickel powder, nickel-titanium alloy powder and aluminum oxide; (2) pressing the mixed material to obtain a pressed product; (3) Sintering the pressed product under the protection of an inert gas, and then cooling it to obtain a sintered alkaline water electrolysis electrode catalyst.
[0007] The beneficial effects of the present invention are: (1) The electrode catalyst prepared by sintering in the present invention has higher mechanical strength and chemical stability, significantly improves the stability of the catalyst under high current density conditions, avoids the problem of the catalyst falling off the substrate, and thus enhances the catalytic performance and service life of the electrode; therefore, the electrode catalyst of the present invention is suitable for the field of alkaline water electrolysis technology, and is particularly suitable for application scenarios that require continuous operation at high current density, such as large-scale hydrogen production and industrial electrolysis.
[0008] (2) The present invention improves the preparation process of the motor catalyst, which not only improves the stability of the catalyst, but also simplifies the production process, reduces the production cost, and promotes the progress and development of alkaline water electrolysis technology.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Furthermore, the electrode catalyst material in step (1) comprises the following raw materials in parts by weight: 65-85 parts of nickel powder, 10-20 parts of nickel-titanium alloy powder and 5 parts of aluminum oxide; The mass content of titanium in the nickel-titanium alloy powder is 10%-20%; The particle size of the nickel powder in the mixed material is 0.5um-5um; the particle size of the nickel-titanium alloy powder in the mixed material is 0.5um-5um; the particle size of the aluminum oxide in the mixed material is 0.1um-3um.
[0011] The beneficial effects of adopting the above further scheme are: the optimized raw material ratio enables the electrode catalyst of the present invention to exhibit excellent catalytic performance and stability under high current density conditions, and the surface structure is dense without obvious cracks or peeling phenomena; the use of alumina as a binder not only enhances the mechanical strength of the catalyst, but also improves the chemical stability of the catalyst.
[0012] Furthermore, the electrode catalyst material in step (1) comprises the following raw materials in parts by weight: 85 parts of nickel powder, 15 parts of nickel-titanium alloy powder and 5 parts of aluminum oxide.
[0013] Furthermore, step (2) is specifically: pressing the mixed material at a pressure of 100±10 MPa for 5-15 minutes to obtain a pressed product. The shape and size of the pressed product are limited as required, and the pressing time can be as long as the density and uniformity requirements of the electrode catalyst are met.
[0014] The beneficial effect of adopting the above further scheme is that the present invention adopts high-pressure pressing to ensure the compactness and uniformity of the catalyst, and avoids the performance degradation caused by internal voids during use.
[0015] Furthermore, step (3) is specifically as follows: sintering the pressed product at 800°C-850°C for 3h-4h under the protection of an inert gas, and then cooling it at room temperature to obtain a sintered alkaline water electrolysis electrode catalyst.
[0016] The beneficial effects of adopting the above further scheme are: the present invention adopts a high-temperature sintering process to enable the electrode catalyst to maintain a stable structure and performance under high temperature conditions, thereby maintaining good catalytic activity under high current density conditions; and adopts natural cooling to room temperature to ensure the structural integrity and stability of the catalyst.
[0017] Furthermore, step (3) is specifically as follows: sintering the pressed product at 850° C. for 4 h under the protection of an inert gas, and then cooling it at room temperature to obtain a sintered alkaline water electrolysis electrode catalyst.
[0018] Furthermore, the inert gas in step (3) includes nitrogen, argon or helium, wherein the nitrogen, argon or helium is a high-purity gas with a purity greater than 99.999%.
[0019] In a second aspect, a sintered alkaline water electrolysis electrode catalyst is provided. The sintered alkaline water electrolysis electrode catalyst is prepared by the preparation method.
[0020] The beneficial effect of adopting the above scheme is that the electrode catalyst prepared by the sintering process of the present invention effectively solves the problem that the catalyst prepared by the existing chemical deposition method is easy to fall off under high current density conditions, and greatly improves the stability and reliability of the catalyst.
[0021] In a third aspect, a sintered alkaline water electrolysis electrode catalyst is used to electrolyze alkaline water.
[0022] The beneficial effects of adopting the above scheme are as follows: experimental data show that when the current density of the electrode catalyst prepared by the present invention is 6000 A / cm²-14000 A / cm², the stability test shows no obvious shedding, the catalytic performance is good, the surface structure is dense, no obvious cracks or peeling phenomena are observed, and the catalytic activity is stable without significant performance degradation after continuous operation for 100 hours at high current density; compared with the catalyst prepared by the chemical deposition method, the catalyst of the present invention shows significant advantages under high current density conditions.
[0023] Furthermore, the sintered alkaline water electrolysis electrode catalyst is used to electrolyze alkaline water at a current density of 6000 A / cm²-14000 A / cm². BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1This is a SEM image of the electrocatalyst prepared in Example 1 of the present invention after continuous operation for 100 hours under the condition of 14000 A / cm²; Figure 2 This is a SEM image of the electrocatalyst prepared in Comparative Example 1 of the present invention after continuous operation for 100 hours at 14000 A / cm². DETAILED DESCRIPTION
[0025] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0026] Example 1 This embodiment relates to a method for preparing a sintered alkaline water electrolysis electrode catalyst, comprising the following steps: (1) Raw material mixing: Weigh the required nickel powder (Ni), nickel-titanium alloy powder (NiTi) and alumina binder (Al 2 O 3 ), the amount of each raw material is shown in Table 1. A ball mill is used to mix the raw materials in a dry environment for 30 minutes to uniformly mix the raw materials to obtain a mixed material.
[0027] (2) Pressing: The mixed material is loaded into a special mold. Press at a pressure of 100 MPa for 10 minutes, and use a hydraulic press to press the powder into a sample of the desired shape and size to obtain a pressed object. During the pressing process, ensure that the pressure is evenly distributed to avoid cracks or deformation.
[0028] (3) Sintering: Pre-introduce high-purity nitrogen (purity greater than 99.999%) into the sintering furnace to remove oxygen and other impurities in the air. Place the pressed object in the sintering furnace and close the furnace door.
[0029] Slowly raise the temperature to 850°C and keep it at this temperature for 4 hours. After sintering, naturally cool to room temperature. Take out the sintered sample, check its appearance quality and dimensional consistency, and obtain a sintered alkaline water electrolysis electrode catalyst. If necessary, perform further processing, such as grinding to remove burrs, etc.
[0030] Embodiment 2-8 Compared with Example 1, except that the amounts of raw materials and preparation conditions recorded in Table 1 are different from those in Example 1, the rest are the same as those in Example 1.
[0031] Table 1 Examples 1-8 Raw materials and preparation conditions Table 2 Comparative Examples 1-4 Raw materials and preparation conditions The catalyst prepared by the chemical deposition method in this comparative example comprises the following steps: (1) Solution preparation: Accurately weigh the required metal salt (nickel sulfate NiSO 4 ) and reducing agent (formaldehyde HCHO). Dissolve the metal salt in deionized water to prepare a series of solutions with a certain concentration of 0.1 M-0.5 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M.
[0032] Meanwhile, the reducing agent was dissolved in deionized water to prepare a series of solutions with concentrations of 0.05M-0.2M, 0.1M, 0.2M, 0.3M, 0.4M, and 0.5M.
[0033] (2) Chemical deposition: Clean the substrate (nickel mesh) and activate it. Immerse the substrate in a solution containing metal salts. Add a reducing agent solution, control the reaction temperature to 60°C, and the reaction time to 2 hours. During this process, stir to ensure that the solution reacts evenly.
[0034] (3) Cleaning and drying: After the reaction is completed, the substrate with the catalyst deposited is taken out and repeatedly rinsed with deionized water. It is placed in an oven and dried at 100°C for 2 hours.
[0035] Compared with Comparative Example 1, the deposition conditions in this comparative example are changed. The catalyst prepared by chemical deposition method comprises the following steps: (1) Solution preparation: Accurately weigh the required metal salt (nickel sulfate NiSO 4 ) and reducing agent (formaldehyde HCHO). Dissolve the metal salt in deionized water to prepare a solution with a concentration of 0.1 M-0.5 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M. At the same time, dissolve the reducing agent in deionized water to prepare a solution with a concentration of 0.05 M-0.2 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M.
[0036] (2) Chemical deposition: Clean the substrate (nickel mesh) and activate it. Immerse the substrate in a solution containing metal salts. Add a reducing agent solution, control the reaction temperature to 70°C, and the reaction time to 3 hours. During this process, stir to ensure that the solution reacts evenly.
[0037] (3) Cleaning and drying: After the reaction is completed, the substrate with the catalyst deposited is taken out and repeatedly rinsed with deionized water. It is placed in an oven and dried at 100°C for 2 hours.
[0038] Without using nitrogen protective atmosphere, the effect of sintering process on catalyst performance was studied. The specific steps are as follows: sintering was performed in an open environment (non-protective atmosphere), and other conditions were consistent with Example 1.
[0039] This comparative example does not add Al 2 O 3 , the specific steps are as follows: (1) Raw material mixing: Weigh the required nickel powder (Ni) and nickel-titanium alloy powder (NiTi). The amount of each raw material is shown in Table 2. Use a ball mill to mix the raw materials in a dry environment for 30 minutes to uniformly mix the raw materials to obtain a mixed material.
[0040] (2) Pressing: The mixed material is loaded into a special mold. Press at a pressure of 100 MPa for 10 minutes, and use a hydraulic press to press the powder into a sample of the desired shape and size to obtain a pressed object. During the pressing process, ensure that the pressure is evenly distributed to avoid cracks or deformation.
[0041] (3) Sintering: Pre-introduce high-purity nitrogen (purity greater than 99.999%) into the sintering furnace to remove oxygen and other impurities in the air. Place the pressed object in the sintering furnace and close the furnace door. Slowly raise the temperature to 850°C and keep it at this temperature for 4 hours. After sintering, naturally cool to room temperature. Take out the sintered sample, check its appearance quality and dimensional consistency, and obtain a sintered alkaline water electrolysis electrode catalyst. If necessary, perform further processing, such as grinding to remove burrs.
[0042] Test example (1) Stability Performance test: Install the prepared samples into an alkaline water electrolyzer. Carry out catalytic performance tests at current densities of 6000 A / cm², 10000 A / cm², and 14000 A / cm². Record the stability data of the catalyst and observe whether there is obvious shedding phenomenon, performance decay rate, and catalyst activity. Shedding phenomenon, performance decay rate, and catalyst activity The shedding test is as follows: (a) The statistical method for shedding phenomenon is as follows: ① Before the test begins, record the initial weight of the electrode.
[0043] ② Under the conditions of test current density of 6000 A / cm², 10000 A / cm², and 14000 A / cm², after each test, the electrode was removed from the electrolytic cell, rinsed with deionized water and dried, and then reweighed.
[0044] ③ Calculate the amount of catalyst shedding by comparing the weight difference of the electrode before and after the test. Shedding rate = (initial weight - weight after test) / initial weight × 100%.
[0045] (b) The performance degradation rate is tested as follows: ① Before the test begins, record the initial catalytic performance (such as catalytic activity) of the electrode at the set current density.
[0046] ②Continuously operate for 100 hours under the set current density conditions and record the catalytic performance data at regular intervals (every 24 hours).
[0047] ③Performance decay rate = (initial performance - performance at the end of the test) / initial performance × 100% (c) The method for detecting the activity of the catalyst is as follows: ①Install the prepared sample into the alkaline water electrolyzer.
[0048] ②The catalytic performance tests were carried out at current densities of 6000 A / cm², 10000 A / cm², and 14000 A / cm² respectively.
[0049] ③Record the catalytic activity (hydrogen production rate) of the electrode at each current density.
[0050] The activity performance of the catalyst was evaluated by comparing the catalytic activity at different current densities.
[0051] (2) Surface roughness The surface roughness detection steps are as follows: ① First, ensure that the surface of the electrode catalyst sample is clean and free of contamination. If necessary, it can be cleaned with an ultrasonic cleaner, and then rinsed thoroughly with deionized water and dried.
[0052] ② Use an instrument with high-precision surface topography measurement capabilities and adopt a scanning electron microscope (SEM) in conjunction with a surface profiler for measurement.
[0053] ③ Fix the cleaned sample on the sample stage of the SEM to ensure that the sample is stable to prevent movement during the measurement process.
[0054] ④ According to the characteristics of the sample and the detection requirements, set the SEM scanning parameters, such as scanning range, resolution, scanning speed, etc., to ensure that the surface details can be accurately captured.
[0055] ⑤Start SEM to scan the surface and collect surface morphology images.
[0056] ⑥ Analyze the collected data through software and extract surface roughness parameters, such as arithmetic mean deviation (Ra), root mean square roughness (Rq), etc. Ensure that the analysis area is representative and covers a large enough surface range to reflect the overall characteristics.
[0057] ⑦ Record the surface roughness value of each sample and save the original data and images for subsequent analysis and verification.
[0058] 2. Experimental results As shown in Table 3, the stability test of the electrode catalysts of Examples 1-8 showed no obvious shedding when the current density was 6000 A / cm², 10000 A / cm², and 14000 A / cm², and the catalytic performance was good. Figure 1 As shown, the catalyst surface structure is dense, with no obvious cracks or peeling. The catalyst runs continuously for 100 hours at high current density, and the catalytic activity is stable without significant performance degradation.
[0059] As shown in Table 3, when the current density of the catalysts of Comparative Examples 1-4 was 6000 A / cm², 10000 A / cm², and 14000 A / cm², the stability test showed that the catalysts began to fall off and the catalytic performance decreased. Figure 2 As shown in the figure, cracks and local peeling appeared on the catalyst surface. After the catalyst was continuously operated at high current density for 100 hours, the catalytic activity was significantly attenuated.
[0060] Table 3 Experimental results In summary, the electrode catalyst prepared by the sintering process of the present invention effectively solves the problem that the catalyst prepared by the existing chemical deposition method is easy to fall off under high current density conditions, and greatly improves the stability and reliability of the catalyst. Experimental data show that when the current density of the electrode catalyst prepared by the present invention is 6000 A / cm²-14000 A / cm², the stability test shows no obvious shedding, good catalytic performance, dense surface structure, no obvious cracks or peeling phenomenon, and continuous operation for 100 hours at high current density, the catalytic activity is stable, and there is no significant performance degradation; compared with the catalyst prepared by the chemical deposition method, the catalyst of the present invention shows significant advantages under high current density conditions.
[0061] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a sintered alkaline water electrolysis electrode catalyst, characterized in that: The steps include: (1) mixing raw materials of various electrode catalyst materials to obtain a mixed material, wherein the electrode catalyst material comprises the following raw materials: nickel powder, nickel-titanium alloy powder and aluminum oxide; (2) pressing the mixed material to obtain a pressed product; (3) Sintering the pressed product under the protection of an inert gas, and then cooling it to obtain a sintered alkaline water electrolysis electrode catalyst.
2. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to claim 1, characterized in that: The electrode catalyst material in step (1) comprises the following raw materials in parts by weight: 65-85 parts of nickel powder, 10-20 parts of nickel-titanium alloy powder and 5 parts of aluminum oxide; The mass content of titanium in the nickel-titanium alloy powder is 10%-20%; The particle size of the nickel powder in the mixed material is 0.5um-5um; the particle size of the nickel-titanium alloy powder in the mixed material is 0.5um-5um; the particle size of the aluminum oxide in the mixed material is 0.1um-3um.
3. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to claim 1, characterized in that: The electrode catalyst material in step (1) includes the following raw materials in parts by weight: 85 parts of nickel powder, 15 parts of nickel-titanium alloy powder and 5 parts of aluminum oxide.
4. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to any one of claims 1 to 3, characterized in that: Step (2) specifically comprises: pressing the mixed material at a pressure of 100±10 MPa for 5-15 minutes to obtain a pressed product.
5. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to any one of claims 1 to 3, characterized in that: Step (3) is specifically as follows: sintering the pressed product at 800°C-850°C for 3h-4h under the protection of an inert gas, and then cooling it at room temperature to obtain a sintered alkaline water electrolysis electrode catalyst.
6. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to claim 5, characterized in that: Step (3) is specifically as follows: sintering the pressed product at 850° C. for 4 hours under the protection of an inert gas, and then cooling it at room temperature to obtain a sintered alkaline water electrolysis electrode catalyst.
7. The method for preparing a sintered alkaline water electrolysis electrode catalyst according to claim 5, characterized in that: The inert gas in step (3) includes nitrogen, argon or helium.
8. A sintered alkaline water electrolysis electrode catalyst, characterized in that: The sintered alkaline water electrolysis electrode catalyst is prepared by the preparation method described in any one of claims 1 to 7.
9. An application of a sintered alkaline water electrolysis electrode catalyst, characterized in that: The sintered alkaline water electrolysis electrode catalyst according to claim 8 is used to electrolyze alkaline water.
10. The use of a sintered alkaline water electrolysis electrode catalyst according to claim 9, characterized in that: The sintered alkaline water electrolysis electrode catalyst is used to electrolyze alkaline water at a current density of 6000 A / cm²-14000 A / cm².